MABĀDI’ ‘ASYRAH SEBAGAI FONDASI ONTOLOGIS HUMANOID ASISTEN GURU PENDIDIKAN AGAMA ISLAM - Ainurrafiq Dawam; Fuad Arif Fudiyartanto; Muhammad Alharis; Soiful Hadi; Muhamamd Adwim Rifqy El-Hisan (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2025)
The transformation of Islamic education in the digital era demands new approaches capable of bridging scholarly tradition and technological innovation. This article examines the reconstruction of Mabādi’ ‘Asyrah—the ten foundational principles of knowledge in Islamic tradition—as an ontological and epistemological framework for designing a Humanoid Assistant for Islamic Religious Education (PAI) Teacher. Employing a reflective qualitative methodology grounded in Islamic educational philosophy, this study integrates classical and contemporary sources to formulate an AI-based learning system that is ethical, spiritual, and contextually attuned. The findings reveal that each principle of Mabādi’ ‘Asyrah can be translated into design elements, interaction modalities, and content structures of the Humanoid, encompassing system definitions, objects of inquiry, and underlying dalīl shar‘ī. This integration significantly reshapes the relationship between teacher, learner, and technology, while opening pathways for the decolonization of Islamic educational technology. By adopting Mabādi’ ‘Asyrah as a guiding framework, the Humanoid Assistant for PAI emerges not merely as a technological tool, but as a pedagogical entity that holistically supports the formation of the insān kāmil.